Wachstafel und Weltformel. Erinnerungspoetik und Wissenschaftskritik in Günter Eichs „Maulwürfen“ - Heydenreich, Aura (Vandenhoeck & Ruprecht, 2007)
For a long time, Gunther Eich's Maulwurfe was classified as nonsense verse. This classification is refuted in this work, and it is shown that Eich's work leads to surprising new ground. It is dedicated to the relationship between the poetics of memory and intertextuality in Eich's later works. The surprisingly high relevance of Eich's poetology on natural sciences is presented, casting Maulwurfe in an entirely new light. German tex